Chile’S Right-Wing Parties in the Post-Pinochet Years: The Rise and Fall of the ‘Lavín’ Style, 2000-2004 [Os Partidos de Direita No Chile No Período Pós-Pinochet: A Ascensão E Queda Do ‘Lavinismo’: 2000-2004] [la Derecha Pinochetista en el Post Pinochetismo: Auge y Crisis del ‘Lavinismo’, 2000-2004] - Valdivia-Ortiz de Zarate, V (Editora da P U C R S, 2016)
This article analyzes the performance of Santiago’s mayor and staunch Pinochet supporter Joaquín Lavín, with the purpose of reviewing right-wing politics in Post-Pinochet Chile. I suggest that de-politicization in Postdictatorial Chile was related to previous municipal reform and the imposition of a “Lavín Style” seeking consensus around neoliberal ideas, and a redefinition of politics as mere problem-solving, or “cosismo”. It is argued that this strategy ultimately failed due to the agenda of Socialist President Ricardo Lagos, who exposed the vacuity of “cosismo” and smoothed the way for the accession of a more liberal right to the presidential seat in 2010. © 2016, Editora da P U C R S. All rights reserved.